2024
DOI: 10.3390/microorganisms12040642
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Effects of Curcumin on the Gut Microbiota: A Potential Strategy for Disease Treatment and Health Promotion

Junwen Zhu,
Lan He

Abstract: Curcumin (CUR) is a lipophilic natural polyphenol that can be isolated from the rhizome of turmeric. Studies have proposed that CUR possesses a variety of biological activities. Due to its anti-inflammatory and antioxidant properties, CUR shows promise in the treatment of inflammatory bowel disease, while its anti-obesity effects make it a potential therapeutic agent in the management of obesity. In addition, curcumin’s ability to prevent atherosclerosis and its cardiovascular benefits further expand its poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 153 publications
(168 reference statements)
0
1
0
Order By: Relevance
“…In addition to its potential anticancer properties, numerous reviews suggest that curcumin can help ameliorate obesity through multiple mechanisms. 17 These include maintaining redox balance, 18 reducing inflammation, 19 modulating gut microbiota, 20 inhibiting adipogenesis, 21 stimulating energy expenditure, 22 and regulating lipid metabolism. 23 Furthermore, our previous study showed that the curcumin degradant, FER, exhibited an anticancer effect, but its potential antiobesity effect has not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its potential anticancer properties, numerous reviews suggest that curcumin can help ameliorate obesity through multiple mechanisms. 17 These include maintaining redox balance, 18 reducing inflammation, 19 modulating gut microbiota, 20 inhibiting adipogenesis, 21 stimulating energy expenditure, 22 and regulating lipid metabolism. 23 Furthermore, our previous study showed that the curcumin degradant, FER, exhibited an anticancer effect, but its potential antiobesity effect has not been discussed.…”
Section: Introductionmentioning
confidence: 99%